United States : Publication of Financial Sector Assessment Program Documentation; Detailed Assessment of Observance of the Fed wire Securities Service's Observance of the CPSS-IOSCO Recommendations for Securities Settlement Systems. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Detailed Assessment of Observance of the Fedwire Securities Service's (FSS) Observance of the Committee on Payment and Settlement Systems/International Organization of Securities Commissions (CPSS-IOSCO) Recommendations for Securities Settlement Systems for the United States. The paper discusses that laws, regulations, rules, procedures, and contractual provisions governing the operations and activities of the FSS are public and readily accessible to system participants. The assessment recommends that securities settlement systems should have a well-founded, clear, and transparent legal basis in the relevant jurisdictions.